Verlust und Wiederauffindung äthiopischer Handschriften aus der Sammlung Rüppell - Tönnies, Bernhard (Aethiopica, 2012)
This article deals with the loss of Ethiopian manuscripts in possession of the Universitätsbibliothek Frankfurt am Main (Sammlung Rüppell) during World War II and the rediscovery of two of these manuscripts in 2010.